A computational scheme for evaluating the phosphorescence quantum efficiency: applied to blue-emitting tetradentate Pt(ii) complexes. Issue 1 (15th July 2021) - Wang, Yu; Peng, Qian; Shuai, Zhigang
Abstract : Phosphorescent organic light-emitting diodes (PhOLEDs) are leading candidates for displays or lighting technologies. Abstract : Phosphorescent organic light-emitting diodes (PhOLEDs) are leading candidates for displays or lighting technologies. Recently, blue phosphorescent tetradentate Pt(ii ) complexes have been attracting extensive attention due to their high phosphorescence quantum efficiency and numerous chemical structures on account of flexible ligand frames and modifications. Using quantum chemistry coupled with our thermal vibration correlation function (TVCF) formalism, we investigated the triplet excited state energy surface and the decay processes involving both direct vibrational relaxation and minimum energy crossing point (MECP) via the transition state ( 3 TS) to the ground state (S0 ) for 16 recently experimentally reported blue-emitting tetradentate Pt(ii ) emitters containing fused 5/6/6 metallocycles. We found that (i) in most cases, the direct vibrational relaxation deactivations dominated the triplet non-radiative decay because either the 3 TS is too high or the MECP is not reachable. Hence, results from the TVCF formalism agreed well with the experiments for the phosphorescence quantum efficiency; (ii) only when both 3 TS and MECP are low, for instance, for PtON1-oMe, deactivations via MECP dominated the triplet non-radiative decay.